The importance of tissue science and valve design in relation to durability and hemodynamics of the DurAVR aortic heart valve - Neethling, William M. L.; Forster, Guenther; Meduri, Christopher; Meuris, Bart; Asgar, Anita W.; Sellers, Stephanie; Cavalcante, João L.; Bapat, Vinayak; Reardon, Michael (Frontiers in Cardiovascular Medicine, 2025)
IntroductionClinical evidence highlighting the efficacy and safety of transcatheter aortic valve replacement (TAVR) and the 2019 Food and Drug Administration (FDA) approval for TAVR in low-risk (younger) patients has created a demand for durable and long-lasting bioprosthetic heart valve (BHV) leaflet materials. Over the life of an implanted BHV mechanical stress, immunogenicity, calcification, and hemodynamic dysfunction lead to failure via structural valve deterioration (SVD). Consequently, the durability of the bioprosthetic materials selected for valve manufacture is of utmost importance.TechnologyThe ADAPT™ tissue engineering process, an anti-calcification preparation that transforms xenograft tissue (bovine pericardium) into a durable valve bioscaffold, shows significant clinical benefits in mitigating the interrelated mechanisms leading to SVD. The novel acellular, biostable and non-calcifying biomaterial has recently been molded into a single-piece 3D biomimetic valve (DurAVR™) with excellent early clinical results and the potential to meet the growing demand of durable BHVs for the treatment of aortic stenosis.DiscussionThe unique design of the DurAVR biomimetic valve in combination with the superior biostability of ADAPT tissue could advance the BHV space by providing superior performance and durability to aortic stenosis patients in need of TAVR.